Uncertain peril genetic engineering and the future of seeds - Cummings, Claire Hope, 1943- (Beacon Press, 2008)
Examines the rise of industrial agriculture and plant biotechnology, the fall of public interest science, and the folly of patenting seeds. The author suggests how green technologies and new approaches to food and farming methods will provide a way out of this growing predicament.